Comparison of Immunomodulation Properties of Porcine Mesenchymal Stromal/Stem Cells Derived from the Bone Marrow, Adipose Tissue, and Dermal Skin Tissue. (21st December 2015) - Ock, Sun-A; Baregundi Subbarao, Raghavendra; Lee, Yeon-Mi; Lee, Jeong-Hyeon; Jeon, Ryoung-Hoon; Lee, Sung-Lim; Park, Ji Kwon; Hwang, Sun-Chul; Rho, Gyu-Jin
Abstract : Mesenchymal stromal/stem cells (MSCs) demonstrate immunomodulation capacity that has been implicated in the reduction of graft-versus-host disease. Accordingly, we herein investigated the capacity of MSCs derived from several tissue sources to modulate both proinflammatory (interferon [IFN] γ and tumor necrosis factor [TNF] α ) and immunosuppressive cytokines (transforming growth factor [TGF] β and interleukin [IL] 10) employing xenogeneic human MSC-mixed lymphocyte reaction (MLR) test. Bone marrow-derived MSCs showed higher self-renewal capacity with relatively slow proliferation rate in contrast to adipose-derived MSCs which displayed higher proliferation rate. Except for the lipoprotein gene, there were no marked changes in osteogenesis- and adipogenesis-related genes following in vitro differentiation; however, the histological marker analysis revealed that adipose MSCs could be differentiated into both adipose and bone tissue. TGF β and IL10 were detected in adipose MSCs and bone marrow MSCs, respectively. However, skin-derived MSCs expressed both IFN γ and IL10, which may render them sensitive to immunomodulation. The xenogeneic human MLR test revealed that MSCs had a partial immunomodulation capacity, as proliferation of activated and resting peripheral blood mononuclear cells was not affected, but this did not differ among MSC sources. MSCs were not tumorigenic when introduced into immunodeficient mice. We concluded that the characteristics of MSCs are tissue source-dependent and their in vivo application requires more in-depth investigation regarding their precise immunomodulation capacities.